Modeling of a Jig Sampling and its Application in Disc Cutter Tools - YAHAYA, SAIFUDIN HAFIZ; HASOLOAN, HAERY IAN PIETER; YAAKOB, MOHD YUHAZRI; HASIB , HAZMAN (iosrjournals.org, 2012)
The operations of preparing the deform sample and round bar mainly consist of the calculation of the bar’s unit weight. The Sampling process is conducted through the two cutting flows such as in line production and disc. The problems are then occurred in the second flow (in disc) in performing the cutting process on a certain length. Modeling of the jig sampling is used to solve this problem and also fully discussed throughout this paper.